Prospects for Drugs Based on the Mitochondria-Targeting Antioxidant SkQ1 in Treatment of Wounds with Impaired Healing - R. A. Zinovkin; E. N. Popova; O. Yu. Pletjushkina; O. P. Ilyinskaya; V. M. Pisarev; B. V. Chernyak (Общая реаниматология, 2018)
Chronic wounds with impared wound healing that require prolong time for healing remain unsolved problem of modern medicine. Excessive oxidative stress plays an important role in the pathogenesis of chronic wounds caused by aging, diabetes and other pathologies. This review is aimed at the role of mitochondria in oxidative stress and to the future prospects for using the innovative mitochondria targeted antioxidants for treatment of impaired wounds. Recent studies in old mice and mice with type 2 diabetes showed that the mitochondrial antioxidant SkQ1 [10- (6'- plastoquinonyl) decyltriphenylphosphonium] stimulates healing of full-thickness dermal wounds. SkQ1 accelerates inflammatory stage of wound healing, maturation of granulation tissue, angiogenesis and epithelization of wounds. The anti-inflammatory effect of SkQ1 is possibly connected to decreased inflammatory activation of the vascular endothelium, which is typical for aging, diabetes and other pathologies. Local administration of SkQ1 also accelerates wound healing and provides strong anti-inflammatory effect in the model of acute aseptic inflammation. In addition, SkQ1 to stimulate apoptosis of neutrophils and suppresses their activation, as well as suppresses inflammatory activation of mast cells. In the wound model in vitro, SkQ1 accelerates movement of epithelial cells and fibroblasts into the «wound» and stimulates differentiation of human subcutaneous fibroblasts to myofibroblasts. Reviewed data suggest that SkQ1-based topical drugs have a great potential to treat wounds that exhibit impaired healing also in patients suffering from chronic critical illness.